Bonding properties of a superatom system with high-Z elements: insights from energy decomposition analysis. Issue 25 (9th April 2020) - Wu, Xiaochen; Gao, Yang; Xie, Weiyu; Wang, Zhigang
Abstract : Superatoms with high- Z elements have novel physicochemical properties, and a comprehensive and thorough view of their bonding properties plays a crucial role in the design of superatoms. Abstract : Superatoms with high- Z elements have novel physicochemical properties, and a comprehensive and thorough view of their bonding properties plays a crucial role in the design of superatoms. Now, energy decomposition analysis shows increasingly prominent performance for understanding inter- and intra-molecular interactions, so the bonding properties of typical superatoms with high- Z elements, Th@Au14, have been investigated here. It is found that under different electron occupation types of the fragments, the electrostatic interaction energy, polarization, and exchange repulsion energy change significantly in their intramolecular interaction energy components, resulting in quantitative or even qualitative differences in their main interaction energy. This indicates that the bonding properties of fragments are related to their electronic structures, and even has extraordinary reference value for the future regulation and control of interactions in superatoms with high- Z elements, which has great significance for superatom development.